Open democracy : reinventing popular rule for the twenty-first century - Landemore, Hélène 1976- (Princeton University Press, 2020)
To the ancient Greeks, democracy meant gathering in public and debating laws set by a randomly selected assembly of several hundred citizens. To the Icelandic Vikings, democracy meant meeting every summer in a field to discuss issues until consensus was reached. Our contemporary representative democracies are very different. Modern parliaments are gated and guarded, and it seems as if only certain people are welcome. Diagnosing what is wrong with representative government and aiming to recover some of the lost openness of ancient democracies, Open Democracy presents a new paradigm of democracy. Supporting a fresh nonelectoral understanding of democratic representation, Hélène Landemore demonstrates that placing ordinary citizens, rather than elites, at the heart of democratic power is not only the true meaning of a government of, by, and for the people, but also feasible and, today more than ever, urgently needed.